DIGITAL TRANSFORMATION AND THE CUSTOMER EXPERIENCE: ENHANCING ENGAGEMENT AND LOYALTY - Antonius Felix; Glisina Dwinoor Rembulan (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This study aims to identify the most basic things in digital transformation, namely what are the factors that can improve customer experience, enhancing engagement and customer loyalty. In an effort to offer in-depth insights on this topic, this research seeks to provide direction for companies focusing on important factors in leveraging digital transformation to create a better customer experience, which in turn will increase their engagement and loyalty. To achieve this goal, this research uses a qualitative approach and case studies from existing literature with the aim of knowing what factors in digital business transformation affect customer experience in order to increase engagement and customer loyalty. This study uses purposive sampling by deep interviewing 11 active consumers from the e-commerce platform under study. Factors such as ease of use, product quality, loyalty programs, exclusive offers, responsive customer support, and special incentives and rewards are key to creating a positive experience, increasing customer engagement and strengthening their loyalty. By understanding and managing these factors, companies can create strong customer relationships, improve customer retention and increase overall business growth.